Territorial narratives of the Aymara community of Chapiquiña in the high mountains of Arica - Leal, Joselin (Revista Chilena de Antropología, 2017)
This article describes the process in which an Aymara community signify their territory in a context of ethnic and territorial claim. It proposes the importance of the territory in the Andes from the pre-Hispanic and colonial period to understand that the Aymara territory is a social and historical construction where memory has played a fundamental role. The analytical categories used were historical, economic and ritual territorial narrative which allow us to propose that the Aymara territory is deterritorialized and reterritorialized through 'the ways of memory' both in urban and rural space.